PENGARUH KREATIVITAS DAN STORE ATMOSPHERE TERHADAP MINAT BELI KONSUMEN PADA CAFE WISATA KAPAL JODOH PAMEKASAN MADURA - Mahmud Mahmud; Awin Mulyati; Rachmawati Novaria (ECONOMOS, 2022)
The development of the business world in Indonesia is increasing over time, as evidenced by the increasing number of companies including café businesses such as the business at the Match Boat Tour cafe that is established and engaged in the culinary business, entrepreneurs are required to be able to think creatively about how to present a variety of places that are different from the ones that are used. others such as the many choices of other cafe places and how to determine the Store Atmosphere that will be used by consumers to get a good place according to the conditions that have been set. More and more competition in the business sector makes companies have to pay attention to what influences buying interest. With the aim that consumers become loyal to the company and provide benefits with better profits for the company. This researcher uses quantitative methods with survey research using questionnaires as the instrument. The population in this study were consumers who had been to the Pamekasan Madura Boat Tour Cafe. The sample of this study used a non-probabilty method (non-random sampling) using a purposive sampling technique with a total of 100 respondents. The data analysis technique used is multiple regression analysis. The results of this study indicate that all independent variables, namely store atmosphere and price, have a positive influence on the dependent variable, namely customer satisfaction.